2022
DOI: 10.3390/bioengineering9120735
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Pomace Extract with Antioxidant, Anticancer, Antimicrobial, and Antiviral Activity Enhances the Quality of Strawberry-Yogurt Smoothie

Abstract: Valorizing the wastes of the food industry sector as additives in foods and beverages enhances human health and preserves the environment. In this study, pomegranate pomace (PP) was obtained from the company Schweppes and exposed to the production of polyphenols and fiber-enriched fractions, which were subsequently included in a strawberry-yogurt smoothie (SYS). The PP is rich in carbohydrates and fibers and has high water-absorption capacity (WAC) and oil-absorption capacity (OAC) values. The LC/MS phenolic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 77 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…In comparison, quercetin IC 50 was 8.9 µg/mL under similar assay conditions (Liu et al, 2020). Pomegranate peel extract inhibited Spike/ACE2 binding by 50% at 0.4-0.6 mg/mL (Alsubhi et al, 2022). Among fruits and vegetables, hot water extracts of soy, tomato, cucumber, and asparagus inhibited >50% Hasegawa et al…”
Section: Pbys and Plant Milks Varied In Isoflavone Profiles And Bioac...mentioning
confidence: 87%
“…In comparison, quercetin IC 50 was 8.9 µg/mL under similar assay conditions (Liu et al, 2020). Pomegranate peel extract inhibited Spike/ACE2 binding by 50% at 0.4-0.6 mg/mL (Alsubhi et al, 2022). Among fruits and vegetables, hot water extracts of soy, tomato, cucumber, and asparagus inhibited >50% Hasegawa et al…”
Section: Pbys and Plant Milks Varied In Isoflavone Profiles And Bioac...mentioning
confidence: 87%
“…Furthermore, the consumption of certain naturally derived dietary products at high levels may decrease the likelihood of tumor recurrence and enhance survival in breast cancer patients [73]. Many nutritional natural products found in the Mediterranean area, including pomegranate [74,75], edible mushrooms [76,77], marine algae [78,79], curcumin [80,81], whole-grain cereals [82,83], citrus fruit [84,85], grapes [86,87], and cucumber [88,89], have been shown in experimental studies to disrupt the development and progression of cancer via the application of anticancer or antineoplastic activity.…”
Section: Fruits Vegetables and Plant-based Foodsmentioning
confidence: 99%
“…It shows a broad spectrum of anti-microbial activity against various pathogenic and multidrug-resistant bacterial strains. Several studies reported that pomegranate peel methanolic extracts had antimicrobial activity against several pathogenic and foodborne bacterial strains like S. aureus, B. cereus, L. monocytogenes, P. aeruginosa, K. pneumonia, E. coli, Salmonella typhi Bacillus megaterium , and B. subtilis ( Table 2 ; Hasan et al, 2018 ; Abou El-Nour, 2019 ; Belgacem et al, 2020 ; Alsubhi et al, 2022 ). Whereas, ethyl acetate crude extract exhibited antibacterial activity in plant pathogenic bacteria ( Xanthomonas gardneri, Pectobacterium carotovorum , and Ralstonia solanacearum ) ( Khaleel et al, 2018 ).…”
Section: Antimicrobial and Antiviral Properties Of Fruit Waste Productsmentioning
confidence: 99%